7-Acetoxyhorminone from Salvia multicaulis Vahl. as Promising Inhibitor of 3-Hydroxy-3-methylglutaryl Coenzyme A (HMG-CoA) Reductase - Serkan Yigitkan; Abdulselam Ertas; Ramin Ekhteiari Salmas; Mehmet Firat; Ilkay Erdogan Orhan (MDPI AG, 2022)
3-Hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase is a key enzyme involved in cholesterol biosynthesis and one of the most important targets for the treatment of hypercholesterolemia. A limited number of studies on the HMG-CoA reductase inhibitory potential of natural products are available. Thus, in the current study, we aimed to test the HMG-CoA reductase inhibitory capacity of extracts from the roots and aerial parts of Salvia multicaulis Vahl., through activity-guided isolation. Our findings revealed that the root extract prepared with dichloromethane-acetone (1:1) showed the highest inhibition (71.97 ± 0.37%) at 100 µg/mL. The extract was then initially fractionated by column chromatography and the obtained fractions were monitored by thin layer chromatography. Fractions which were similar to each other were combined and a total of 15 fractions were obtained. Further conventional chromatographic studies were carried out on the active fractions. Based on these fractions, 10 known compounds, comprising 9 terpenes and 1 steroid derivative in total, were isolated and their structures were verified by a combination of IT-TOF-MS, and 1D and 2D NMR techniques. According to the enzyme inhibition data of the identified compounds, 7-acetoxyhorminone exerted the highest inhibition (84.15 ± 0.10%, IC50 = 63.6 ± 1.21 µg/mL). The molecular docking experiments on 7-acetoxyhorminone and horminone indicated that both compounds strongly bind to the active site of the enzyme.